Enhancing Eleventh-Grade Students’ Speaking Proficiency through the ELSA Speak Application: A Pre-Experimental Study - Shofiyah Dinda Yudiramanda; Elyza Martiarini; Dwi Rorin Mauludin Insana (Journal of English Education, 2025)
This study aims to determine the effect of using the ELSA Speak application on the English-speaking skills of 11th-grade students at SMK Tri Sukses Depok. The method used is a pre-experimental design with a one-group pre-test and post-test design. The sample consisted of 30 students selected using purposive sampling. The instrument used was an English-speaking test administered before and after the use of the ELSA Speak application. The data were analyzed using descriptive statistics to obtain the mean scores of the pre-test and post-test, followed by an inferential analysis employing a paired sample t-test to determine whether the improvement in scores was statistically significant. The results showed that the average pre-test score was 48.63, while the post-test average was 69.03. The t-test showed that tcount (5.30) > ttable (1.67), meaning that H₁ is accepted. Thus, it can be concluded that the use of the ELSA Speak application has a significant effect on improving students’ English-speaking skills. The application is effective as a supplementary learning tool in English language instruction.